Horny for Ghost : The Sexualized Remediation of Call of Duty : Modern Warfare II on TikTok - Ask, Kristine; Sihvonen, Tanja (Sage publications, 2024)
After the release of Call of Duty: Modern Warfare II in November 2022, a new, and rather unexpected, following of women and queer fans on TikTok emerged. Centering on the character Simon “Ghost” Riley, they latched onto the tall, muscular, and masked soldier with soulful eyes. Through fannish creations on TikTok, the game's characters and world was de- and re-constructed as a playful space for romantic and sexual imaginings that challenge the cis-het military masculinity of the series. Based on a 6-month netnography, the article explores the fan remediation of Call of Duty in negotiation with TikTok's affordances. We analyze how new fans positioned themselves against traditional fans through weaponization of fangirl practices, how game mechanics were used in unusual ways to generate audiovisual material, and how some of the complex fan-industry relationships manifested as a response to this unexpected fandom.
Keywords: remediation; gender; games; video; fan art; fandom; TikTok; fi=Viestintätieteet|en=Communication Studies|